Peran Lingkungan dan Hubungan Rekan Kerja dalam Meningkatkan Kinerja Karyawan PT. Pilar Blessing Indonesia di Karawang (International Forum of Researchers and Lecturers, 2025)
Relationships between coworkers are one of the important elements in the work environment that affect employee performance. A harmonious work environment and good social relations can create psychological comfort, increase motivation, and encourage effective teamwork. This study aims to determine the effect of the environment of coworkers on employee performance at PT. Pilar Blessing Indonesia located in Karawang. The method used is a descriptive qualitative approach with data collection through observation, interviews, and documentation. The results of the study indicate that relationships between coworkers based on mutual trust, openness, and smooth communication can improve individual and team performance. Conversely, less harmonious work relationships can reduce work enthusiasm and hinder productivity. These findings indicate the importance of managing interpersonal relationships in the workplace as part of a strategy to improve overall organizational performance.